A Review of in vitro Platforms for Understanding Cardiomyocyte Mechanobiology - Chin, Ian L.; Hool, Livia; Choi, Yu Suk (Frontiers in Bioengineering and Biotechnology, 2019)
Mechanobiology - a cell’s interaction with its physical environment – can influence a myriad of cellular processes including how cells migrate, differentiate and proliferate. In many diseases, remodelling of the extracellular matrix (ECM) is observed such as tissue stiffening in rigid scar formation after myocardial infarct. Utilising knowledge of cell mechanobiology in relation to ECM remodelling during pathogenesis, elucidating the role of the ECM in the progression – and perhaps regression – of disease is a primary focus of the field. Although the importance of mechanical signalling in the cardiac cell is well appreciated, our understanding of how these signals are sensed and transduced by cardiomyocytes is limited. To overcome this limitation, recently developed tools and resources have provided exciting opportunities to further our understandings by better recapitulating pathological spatiotemporal ECM stiffness changes in an in vitro setting. In this review, we provide an overview of a conventional model of mechanotransduction and present understandings of cardiomyocyte mechanobiology, followed by a review of emerging tools and resources that can be used to expand our knowledge of cardiomyocyte mechanobiology towards more clinically relevant applications.